2012
DOI: 10.2174/1570159x11209040354
|View full text |Cite
|
Sign up to set email alerts
|

Redox Signaling Pathways Involved in Neuronal Ischemic Preconditioning

Abstract: There is extensive evidence that the restoration of blood flow following cerebral ischemia contributes greatly to the pathophysiology of ischemia mediated brain injury. The initiating stimulus of reperfusion injury is believed to be the excessive production of reactive oxygen (ROS) and nitrogen (RNS) species by the mitochondria. ROS and RNS generation leads to mitochondrial protein, lipid and DNA oxidation which impedes normal mitochondrial physiology and initiates cellular death pathways. However not all ROS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 85 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…Nrf2 is a key transcription factor that regulates antioxidant genes as an adaptive response to oxidative stress or pharmacological stimuli. 30 To investigate the effect of 5d on the Nrf2 signaling, the cellular locations of Nrf2 and kelch-like ECHassociated protein 1 (Keap-1) were evaluated aer I/R. Immunoblot analysis revealed that the expression of Nrf2 in the nuclear fraction was signicantly higher in 5d-treated groups than in the Model group.…”
Section: D Protects Primary Cultured Cortical Neurons Against Ogd/rin...mentioning
confidence: 99%
“…Nrf2 is a key transcription factor that regulates antioxidant genes as an adaptive response to oxidative stress or pharmacological stimuli. 30 To investigate the effect of 5d on the Nrf2 signaling, the cellular locations of Nrf2 and kelch-like ECHassociated protein 1 (Keap-1) were evaluated aer I/R. Immunoblot analysis revealed that the expression of Nrf2 in the nuclear fraction was signicantly higher in 5d-treated groups than in the Model group.…”
Section: D Protects Primary Cultured Cortical Neurons Against Ogd/rin...mentioning
confidence: 99%
“…Excessive ROS production during cerebral I/R injury causes cellular and molecular oxidative injury, exacerbating both cardiac and cerebral tissue damage [ 1 ]. ROS play a pivotal role in coordinating several deleterious processes that contribute to lipid peroxidation, DNA fragmentation and protein oxidation and preferentially damage highly oxygenated cells [ 2 , 3 ]. Oxidative events observed in myocardial tissues after stroke have been associated with arrhythmogenesis, depressed contractility and myocardial remodeling, highlighting the profound effect that cerebral events have on cardiac function and vice versa [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%